Does YouTube provide high-quality resources for patient education on atrial fibrillation ablation?. (1st December 2018) - Camm, C. Fielder; Russell, Emily; Ji-Xu, Antonio; Rajappan, Kim
Abstract: Objective: Catheter ablation has a role in the treatment of selected patients with atrial fibrillation (AF). Patients are increasingly utilising the internet as an education resource. However, there is limited oversight on online patient information. This study aimed to determine the quality of video-based patient education resources for catheter ablation in AF. Methods: YouTube was searched for "Ablation" and one of "Atrial Fibrillation" or "AFib" or "AF" (a total of three searches). Videos were included if they discussed catheter ablation and excluded if they primarily discussed surgical/hybrid ablation or were non-English language. Each video was scored by two authors for compliance with a gold-standard item set created from patient booklets from the Arrhythmia Alliance. Results: A total of 6357 videos were identified from all searches. Of these, a total of 111 videos met inclusion criteria and were included in the analysis. The median number of views for each video was 1794.5 (IQR 335 to 10, 972) with a median duration of 217 s (IQR 135 to 444 s). The median number of essential criteria found in each video was 4/21 (IQR 3 to 6), and no video met all the essential criteria. Video score was not significantly correlated with video likes or number of views. Conclusions: No available videos provide sufficiently detailed information for a patient to have a reasonable understanding of catheter ablation. A lack of correlation between views/'likes' and video score suggests patients are unable to critically evaluate these resources for educational content. Highlights: The quality of video-based catheter ablation education material is generally poor. Views and 'likes' are not strongly correlated with video quality. Patients should be warned about the inaccuracies in online patient education videos.